Hubungan Pengetahuan Ibu dan Dukungan Suami terhadap Kelengkapan Imunisasi Dasar pada Balita di Kelurahan Maharani - Desvitasari, Ririt; Wati, Yesi Septina; Rahmita, Hirza; Desriva, Nia (Pusat riset dan Inovasi Nasional, 2026)
The coverage of Complete Basic Immunization (Imunisasi Dasar Lengkap or IDL) in Maharani Village remains low at 38.8%, falling short of the national target of 95%. This condition increases the health risk of toddlers contracting Vaccine-Preventable Diseases (PD3I). This study aimed to determine the relationship between mothers' knowledge and husbands' support regarding the completeness of basic immunization for toddlers in Maharani Village, within the working area of Rumbai Bukit Public Health Center. This research employed a quantitative analytic method with a cross-sectional design. The population in this study comprised all mothers with toddlers in the area, with a sample of 73 respondents selected using the purposive sampling technique. Data collection was conducted using validated questionnaires and observation of Maternal and Child Health (KIA) books, followed by univariate and bivariate analysis using the Chi-square statistical test. The results indicated that the majority of toddlers had incomplete immunization status (61.6%), mothers had a low level of knowledge (61.6%), and respondents did not receive support from their husbands (58.9%). Statistical test results confirmed a very significant relationship between mothers' knowledge (p-value = 0.000) and husbands' support (p-value = 0.000) with the completeness of basic immunization. The conclusion confirms that knowledge and husband's support are the main determinant factors. It is suggested that Rumbai Bukit Public Health Center implement a more inclusive health promotion strategy by involving the active role of husbands in monitoring child health.